Adsorption of long-chain alkanethiols on Au(111): a look from the substrate by high resolution X-ray photoelectron spectroscopy - Chesneau, Frédérick; Zhao, Jianli; Shen, Cai; Buck, Manfred; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2010)
The structure of the interface between a self-assembled monolayer (SAM) of alkanethiolates (AT) and the underlying Au(111) substrate is a longstanding puzzle in surface science. To cast further light on this problem, we took SAMs of hexanethiolate and dodecanethiolate on Au(111) as test systems and studied them by a combination of synchrotron-based high resolution X-ray photoelectron spectroscopy (HRXPS) and scanning tunneling microscopy (STM). The emphasis of the HRXPS characterization was put on the Au 4f emission of the substrate, which could be decomposed into the components related to the bulk and surface. The behavior of the surface component upon formation of hexanethiolate and dodecanethiolate SAMs was monitored in detail. We observed both a shift of this component and its branching into two independent emissions, which can be associated with two groups of Au atoms differently affected by the adsorption. This behavior, along with the relative intensity of both surface emissions, was correlated with most probable adsorption configurations of the thiolate headgroups. The analysis of the HRXPS data provides strong evidence for the involvement of the Au-adatoms, similar to the most recent models for short-chain AT monolayers on Au(111). The results indicate, however, that the structure of the long-chain systems is somewhat different and presumably more complex.